2008
DOI: 10.1111/j.1442-200x.2008.02554.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype correlation in children with familial Mediterranean fever in a Turkish population

Abstract: M694V homozygosity is associated with phenotype II and amyloidosis compared to other common genotypes in patients with FMF. Despite current knowledge on FMF, prospective clinical studies with large numbers of patients and different ethnic groups will help us to clarify this considerable disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
53
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 16 publications
18
53
1
6
Order By: Relevance
“…2,[6][7][8][9][10] In addition, the age of the di se a se on set and the di ag no sis we re fo und to be smaller compared to lar ge stu di es and si mi lar to a study from Tur key. 2,9,11 In our se ri es, abdo mi nal pa in was the most com mon fe a tu re (97.7%), fol lo wed by fe ver (72.4%) and jo int in volve ment (58.6%). The se fin dings we re si mi lar to the re sults of ot her stu di es on Turkish and Jewish so cie ti es.…”
Section: Discussionmentioning
confidence: 67%
“…2,[6][7][8][9][10] In addition, the age of the di se a se on set and the di ag no sis we re fo und to be smaller compared to lar ge stu di es and si mi lar to a study from Tur key. 2,9,11 In our se ri es, abdo mi nal pa in was the most com mon fe a tu re (97.7%), fol lo wed by fe ver (72.4%) and jo int in volve ment (58.6%). The se fin dings we re si mi lar to the re sults of ot her stu di es on Turkish and Jewish so cie ti es.…”
Section: Discussionmentioning
confidence: 67%
“…In other studies, the prevalence of M694V mutation was reported as 48%, 71.3% and 74.3%, respectively (Yilmaz et al 2001;Ertekin et al 2005;Inal et al 2008). Phenotype and genotype correlation in FMF has not been explained definitely, but an increased risk of amyloidosis among M694V homozygotes was reported (Paut et al 2000;Yilmaz et al 2003;Dusunsel et al 2008). A recent research showed that the homozygous for M694V and the compound heterozygous for M694V were associated with a severe clinical course of FMF (Inal et al 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Recent Turkish FMF Study Group records (including both adults and children) document a 1.2:1 (male: female) ratio. 8 The most serious complication of disease is amyloidosis, caused by tissue deposition of serum amyloid A, most notably in kidneys that ultimately leads to end-stage renal failure. 9 The type of mutation has been suggested to establish the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…1 Two major studies from Turkey find no association between the development of amyloidosis and M694V homozygosis, but according to study of Düşünsel et al, M694V homozygote genotype clearly forms a predisposition to development of amyloidosis. 8 The associations of M694V homozygosis with a more severe form of the disease and with a higher frequency of amyloidosis is reported although genotype-phenotype correlation is not well established. Nevertheless, in several other studies, the association of M694V mutation seems not prevalent among FMF patients, especially in Turks.…”
Section: Discussionmentioning
confidence: 99%